Pengelompokan Daerah di Jawa Timur Berbasis Indikator Kesejahteraan Masyarakat dengan Pendekatan Analisis Cluster Hierarki dan Nonhierarki - Muhammad Fikry Al Farizi; Faradilla Harianto; Maria Setya Dewanti; Cynthia Anggelyn Siburian; M. Fariz Fadillah Mardianto; Dita Amelia; Elly Ana (Inferensi, 2023)
Based on Central Statistics Agency (BPS) data in September 2021, East Java is a province with the largest number of poor people in Indonesia with a total of 26,503 million people. Poverty is one of the factors that affect people's welfare in East Java. Therefore, this research was conducted to classify regencies and cities in East Java based on indicators of community welfare through a hierarchical cluster analysis approach using the single linkage, complete linkage, average linkage, and ward methods, determine the optimum cluster for each method using Pseudo – F, then compare the four methods and determine the best method using the rated value, as well as identify the characteristics of each cluster group based on the best method. There are six variables that will be used in this study. All variable data is secondary data obtained from the official website of the Central Statistics Agency (BPS) of East Java Province. This study produced four clusters using the average linkage method as the best method. This research is expected to be useful as a consideration for evaluating the government and related agencies to overcome the main problems that still occur in each regency and city. Thus, the welfare of the people of East Java can be realized and the SDGs targets in Indonesia can be achieved.